Roh Antikristus Menurut 1 Yohanes 2:18-27 dan Keberadaannya dalam Masyarakat Post-Modernisme - Meyta Rosalin Kapoh; Otieli Harefa (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2024)
Discussing the end times will not escape discussing the antichrist because he is the central figure as a sign that the end times have come into effect. The Apostle John in 1 John 2 has specifically warned that the Antichrist will come and the spirit of the antichrist is already at work. The signs of the antichrist spirit according to this passage include: denying Jesus as the Christ and denying the Father who sent Him; rejecting that Jesus Christ has come in the flesh; and all of this begins within the community of believers. The movements that characterise postmodernism have strong indications of being influenced by the spirit of the antichrist that makes man the centre of life and denies the existence and sovereignty of God. Using a descriptive qualitative research method, this paper aims to expose the antichrist, specifically the spirit of antichrist that works in postmodernist society. With the spirit of postmodernism, society deconstructs christianity, relativises the truth of the Bible and even pluralises the way of salvation. All this is the work of the spirit of antichrist. Believers must truly abide in the teaching of the Bible, which is the Word of God, and live under the guidance of the Holy Spirit to withstand the influence of the antichrist spirit.AbstrakMembahas akhir zaman tidak akan luput dari membahas antikristus karena merupakan tokoh sentral sebagai pertanda zaman akhir telah berlaku. Rasul Yohanes dalam 1 Yohanes 2 telah secara spesifik mengingatkan bahwa Antikristus akan datang dan roh antikristus sudah bekerja. Tanda-tanda roh antrikristus menurut perikop ini antara lain; memungkiri Yesus sebagai Kristus dan memungkiri Bapa yang mengutusNya; menolak bahwa Yesus Kristus sudah datang sebagai manusia; dan semua ini diawali dari dalam komunitas orang percaya. Pergerakan-pergerakan yang menjadi ciri postmodernisme berindikasi kuat dipengaruhi oleh roh antikristus yang menjadikan manusia sebagai pusat kehidupan dan memungkiri keberadaan dan kedaulatan Allah. Dengan metode penelitian deskriptif qualitatif, tulisan ini bertujuan memaparkan antikristus, secara khusus roh antikristus yang bekerja dalam masyarakat postmodernisme. Dengan semangat postmodernisme, masyarakat men-dekonstruksi kekristenan, me-relatifkan kebenaran Alkitab bahkan mem-pluralkan jalan keselamatan. Semua ini adalah pekerjaan roh antikristus. Orang percaya harus sunguh-sungguh tinggal dalam pengajaran Alkitab yang adalah Firman Allah dan hidup dalam tuntunan Roh Kudus untuk dapat bertahan dari pengaruh roh antikristus.